The Berenstain bears get the gimmies - Berenstain, Stan (U.S.A : Random House, 1988)
Gran and gramps come up with a plan to help selfish brother and sister bear get rid of a bad case of the galloping greedy gimmies
Keywords: Selfishness - fiction; Behavior - fiction